Implementation Of Automation Process In Generating Cad Model For Rim Wheel - Ali, Mohd Basri; Sugumar, Dharmalingam; Shafie, Azhar; Mohd Daud, Mohd Ahadlin; Zakaria, Kamarul Ariffin; Abd Latif, Mohd Juzaila (Asian Research Publishing Network (ARPN), 2018)
The purpose of this study is to develop a Computer Aided Drawing (CAD) program that allow automation process in CAD software to generate three-dimensional models automatically. Automation process has been widely used and received give positive feedback in various industries due to its convenience in drawing process and time saving. It also provides high reliability, more accurate and also allow multiple task in design creation. The process consists of two stages which are the construction process of rim wheel model using Computer Aided Three-dimensional Interactive Application (CATIA) software and the model automation coding development process. The rim wheel model was constructed and recorded in CATIA Macros tool. The recorded data was then utilized to develop the coding script for the model automation process using Visual Basic language. The important parameters were identified and edited in the coding script to generate the basic shape of the model and other features. The final model supposed to have an ability to alter into three different rim wheel design with different parameters and dimensions. This program could be used as the future platform to fulfill specific customer requirement of a desired product.